Advocacy and Objectivity in Science - Armstrong, J. Scott (Management Science, 1979)
Three strategies for scientific research in management are examined: advocacy, induction, and multiple hypotheses. Advocacy of a single dominant hypothesis is efficient, but biased. Induction is not biased, but it is inefficient The multiple hypotheses strategy seems to be both efficient and unbiased. Despite its apparent lack of objectivity, most management scientists use advocacy. For example, 2/3 of the papers published in a sampling of issues of Management Science (1955–1976) used advocacy. A review of the published empirical evidence indicates that advocacy reduces the objectivity of the scientists. No evidence was found to suggest that this lack of objectivity could be overcome by a “marketplace for ideas” (i.e., publication for peer review). It is recommended that the method of multiple hypotheses be used.